G. V. Kocherha: THE DERIVATIVE TRANSFORMATION OF THE DENOMINATIVE VERBS IN THE EAST SLAVIC WRITTEN MONUMENTS OF XIV – XVII CENTURIES: COGNITIVE-ONOMASIOLOGICAL ASPECT - Kocherha, G. V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
The article is devoted to the study of the denominative verb derivatives in the East Slavic written monuments of the XIV–XVII centuries. The linguo-mental mechanism of secondary notation (denominative derivatives) is established, which occurs at the stage of internal programming, where the connections of the primary value of the sign present in the language with its secondary value. Conceptual modeling of motivational processes of modular denominative verbs contains relations of thought model, images, mental functions and archetypes of the collective unconscious. The cognitive-onomasiological mechanism of modal motivation of the denominative verb derivatives is singled out, which outlines the motivational connection of onomasiological structure and semantics of verb nominees with structures of knowledge about the object of nomination.